Postoperative delirium assessed by post anesthesia care unit staff utilizing the Nursing Delirium Screening Scale: a prospective observational study of 1000 patients in a single Swiss institution. Issue 1 (December 2015) - Winter, A.; Steurer, MP.; Dullenkopf, Alexander
Abstract Background Delirium has become better studied, but is still only partially understood and significantly underestimated. There are some well-known risk factors, but little is known about the incidence of delirium in the diverse patient population of a post anesthesia care unit (PACU). The aim of this study was to investigate the presence of delirium using the Nursing Delirium Screening Scale (NU-DESC). Methods 1000 consecutive patients in the PACU were prospectively evaluated at the point when being ready to be transferred to the normal ward by the registered nurses of the PACU. Results The data of 1, 000 patients was recorded. 242 of the patients (24.2 %) were preoperatively classified as ASA I physical status, 664 patients (66.4 %) as ASA II. A total of 43 patients (4.3 %) presented with a delirium at the time point where they would have been transferred to the normal ward (138.4 ± 55.2 min after arrival in the PACU). 287 patients (28.7 %) of the entire group were over the age of 70 years. Considering only this subgroup, delirium was diagnosed in 30 individuals (10.5 %). Conclusions Delirium screening with the NU-DESC, collected by nursing staff of a PACU is easily feasible and demonstrated a low incidence of delirium in the presented setting. Trial registration German Clinical Trials Register (Deutsches Register Klinischer Studien, www.drks.de ;DRKS 000005426 ; date of registration 4th December 2013).